If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y = y + 3 + 1 Reorder the terms: 3y = 3 + 1 + y Combine like terms: 3 + 1 = 4 3y = 4 + y Solving 3y = 4 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 3y + -1y = 4 + y + -1y Combine like terms: 3y + -1y = 2y 2y = 4 + y + -1y Combine like terms: y + -1y = 0 2y = 4 + 0 2y = 4 Divide each side by '2'. y = 2 Simplifying y = 2
| .03(x+40)+12.8=.4(10-x)+96 | | (3x-5)(-5)= | | 27x^2-246x-240= | | 6(5-x)-3(x-4)=6 | | p^2+p-20=0 | | 46-11=5(x-8) | | 6x^2-x+3=0 | | 4x^2-10x+25=49 | | 64-6x=12x+16 | | 10x^2-80x= | | 12-8x=111-29 | | 8w^3-3w+1=0 | | 4(2-3x)-30=10-2(x-4) | | 27x-30x=7-10 | | 9/x=15/35 | | 4v-16=48 | | 14x^2+26x-48= | | 4x^2+27+35=0 | | 1/3x-1/2=5/6x | | 5x-25x-70=0 | | 2x^7=12 | | 5=8x-11 | | p^6+65p^3+64=0 | | n^2=24-5n | | 10x-70=130 | | 40xy=15y | | -4/9x=-8/27 | | 15x^2-145x+200= | | -3/4m+3=-12 | | 2x+7-4=4x+3-6x | | 5x^2-10xy= | | 5x^2+6x= |